War and Entrepreneurship: A Synthetic Control Study of the Russia-Ukraine Conflict - David B. Audretsch; Paul P. Momtaz; Hanna Motuzenko; Silvio Vismara (Center for Economic Studies and ifo Institute (CESifo), 2023)
Entrepreneurs are often situated in extreme environments characterized by violent conflict. Yet, war is largely a blind spot in entrepreneurship scholarship. As a first step to closing this gap, we offer a well-identified synthetic control study of entrepreneurial dynamics in the Russo-Ukrainian war. Relative to the synthetic counterfactual, Ukraine's number of self-employed dropped by 20%, and the number of Ukrainian SMEs temporarily dropped by 14% but recovered within five years of the start of the conflict. In contrast, Russia had lost more than 1.4 million SMEs (42%) five years into the conflict. The disappearance of entrepreneurs is driven by both fewer new SMEs created and more existing SME closures. To pave the way for systematic scholarship on "war and entrepreneurship," our study proposes a conceptual framework integrating conflict into the theory of entrepreneurial choice and suggests numerous avenues for future research.
Keywords: D74; L26; N44; O17; 330; entrepreneurship; war; Russia-Ukraine conflict